Coumestrol ameliorates doxorubicin-induced cardiotoxicity via activating AMPKα. (1st September 2020) - Wu, Zhen-Zhong; Rao, Min; Xu, Si; Hu, Hong-Yao; Tang, Qi-Zhu
Abstract: Doxorubicin (DOX) acts as the cornerstone in multiple tumour chemotherapy regimens, however, its clinical application is often impeded due to the induction of a severe cardiotoxicity that eventually provokes left ventricular dysfunction and congestive heart failure. Coumestrol (CMT) is a common dietary phytoestrogen with pleiotropic pharmacological effects. The present study aims to investigate the role and mechanism of CMT on DOX-induced cardiotoxicity. Mice were intragastrically administrated with CMT (5 mg/kg/day) for consecutive 2 weeks and then received a single intraperitoneal injection of DOX (15 mg/kg) to mimic the clinical toxic effects after 8-day additional feeding. To verify the role of 5′ AMP-activated protein kinase alpha (AMPKα), AMPKα2 global knockout mice were used. H9C2 cells were cultured to further validate the beneficial role of CMT in vitro . CMT administration notably ameliorated oxidative damage, cell apoptosis and cardiac dysfunction in DOX-treated mice. Besides, we observed that DOX-induced reactive oxygen species overproduction and cardiomyocyte apoptosis were also reduced by CMT incubation in H9C2 cells. Mechanistically, CMT activated AMPKα and Ampkα deficiency abolished the beneficial effects of CMT in vivo and in vitro . Finally, we proved that protein kinase A (PKA) was required for CMT-mediated AMPKα activation and cardioprotective effects. CMT activated PKA/AMPKα pathway to alleviate DOX-induced oxidative damage, cell apoptosis and cardiac dysfunction. Our findings provide a promising therapeutic agent for cancer patients receiving anthracycline chemotherapy.